Multilayer film with soluble bonding layer and method for dissipation
By using a soluble bonding layer in the multilayer film, the problem of difficulty in recycling and reuse of the existing multilayer film structure is solved, and effective separation and reuse of the multilayer film is achieved.
Patent Information
- Application Number
- CN202180034725.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-11
- Filing Date
- 2021-05-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-05-10
AI Technical Summary
The existing multilayer film structures are difficult to recycle and reuse because adhesives between the materials are difficult to separate, and hot melt adhesives are not suitable as part of the multilayer film structure.
A multilayer film structure with a soluble bonding layer, wherein the soluble bonding layer comprises at least 10% by weight of neutralized ethylene acrylic acid copolymer, which can be separated in an aqueous caustic washing liquid to achieve separation and reuse of the multilayer film.
By introducing a soluble bonding layer into the multilayer film, effective separation and reuse of the multilayer film is achieved, and the recycling rate of the material is improved.
Smart Images

Figure CN115461215B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Patent Application Serial No. 63 / 022,669, filed on May 11, 2020, and entitled “Multilayer Film Having a SolubleTie Layer and Method For Dissipating,” the entire contents of which are incorporated herein by reference. Background Art
[0003] The subject matter disclosed herein relates to multilayer films containing soluble tie layers and methods of dissolving such film layers.
[0004] Typically, multilayer membrane structures made of different materials prove difficult to recycle and reuse. These materials are not easily separated, and therefore it is difficult to obtain relatively pure materials from the multilayer membrane.
[0005] Although it is known that hot melt adhesives can be dissolved in caustic washing liquids, hot melt adhesives are not suitable for extrusion as a part of a multilayer film structure. In addition, hot melt adhesives are still not suitable for use as a tie layer in a multilayer film structure.
[0006] Therefore, a multilayer membrane that can be separated in an aqueous caustic wash to facilitate recycling is desired.The layers of the multilayer membrane are extruded and therefore the materials used must be extrudable at processing temperatures, provide sufficient bond strength and allow separation in an aqueous caustic wash.
[0007] The above discussion provides general background information only and is not intended to be used as an aid in determining the scope of the claimed subject matter. Summary of the invention
[0008] A multilayer film having a soluble tie layer and a method for dissipating the soluble tie layer from the multilayer film are disclosed. The multilayer film has a first outer layer; a first soluble tie layer, the first soluble tie layer comprising at least 10 weight percent, at least 40 weight percent, or at least 50 weight percent of a neutralized ethylene acrylic acid copolymer. When placed in a caustic solution, the soluble tie layer dissipates from the multilayer film.
[0009] An advantage that may be realized in some disclosed embodiments implementing a soluble tie layer is that it allows separation of the multi-layer film structure to aid in reuse and recycling.
[0010] In an exemplary embodiment, a multilayer film is disclosed. The multilayer film comprises a first outer layer; a first soluble tie layer adhered to two adjacent layers, the first soluble tie layer comprising at least 10 wt%, at least 20 wt%, at least 30 wt%, at least 40 wt%, or at least 50 wt% of ethylene acrylic acid copolymer, ethylene methacrylic acid copolymer, or a blend thereof, 20-90% of which is neutralized; and a second outer layer. The soluble tie layer is disposed between the first and second outer layers, the soluble tie layer adhered to the two adjacent layers, wherein the bond strength is at least 2.5 N / 15mm, 3.0 N / 15mm, 3.5 N / 15mm, 4.0 N / 15mm, 4.5 N / 15mm, or 5.0 N / 15mm as measured according to ASTM F904. When the multilayer film is prepared and tested, at least 90 wt % of the soluble tie layer dissipates from the multilayer film within 30, 25, 20, 15 minutes at temperatures of 45°C, 55°C, 65°C, 75°C, 85°C, 95°C in a caustic solution containing 1 wt % sodium hydroxide, and the remaining parameters are according to APR Tensile Test Standard PET-P-00.
[0011] In another exemplary embodiment, the multilayer film comprises a first outer layer; a first soluble tie layer adhered to two adjacent layers, the first soluble tie layer comprising at least 10 wt%, at least 20 wt%, at least 30 wt%, at least 40 wt%, or at least 50 wt% of ethylene acrylic acid copolymer, 20-90% of which is neutralized; and a second outer layer. The soluble tie layer is disposed between the first and second outer layers, the soluble tie layer adhered to the two adjacent layers, wherein the bond strength is at least 2.5 N / 15mm, 3.0 N / 15mm, 3.5 N / 15mm, 4.0 N / 15mm, 4.5 N / 15mm, or 5.0 N / 15mm as measured according to ASTM F904. The linear dissolution rate of the first soluble tie layer in a 1 wt% NaOH solution at 85°C is at least 0.004 in / min as measured according to APR Tensile Test Standard PET-P-00.
[0012] In another exemplary embodiment, a method for separating at least one layer of a multilayer film is disclosed. The method includes the following steps: providing a multilayer film; the multilayer film comprises a first outer layer and a second outer layer and a soluble tie layer adhered to two adjacent layers, the first soluble tie layer comprising at least 10 wt%, at least 20 wt%, at least 30 wt%, at least 40 wt%, or at least 50 wt% of ethylene acrylic acid copolymer, 20-90% of which is neutralized; shredding or grinding the multilayer film; subjecting the multilayer film to a caustic solution for at least 30, 25, 20, 15, or 10 minutes; the caustic solution is at an elevated temperature in any one of the following ranges or between any one of the following ranges: 40-50°C, 50-60°C, 60-70°C, 70-80°C, 80-90°C, 90-100°C to cause the soluble tie layer to dissipate from the multilayer film, resulting in dissolved and solid components of the multilayer film in the caustic solution; and collecting the solid components from the caustic solution. In the caustic solution, at least 90 weight percent of the soluble tie layer dissipates from the multilayer film.
[0013] This summary of the invention is intended only to provide a brief overview of the subject matter disclosed herein according to one or more illustrative embodiments, and is not intended to be used as a guide for interpreting the claims or to define or limit the scope of the invention, which is limited only by the appended claims. This summary is provided to introduce an illustrative selection of concepts that will be further described in the following detailed description in a simplified form. This summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used as an aid in determining the scope of the claimed subject matter. The claimed subject matter is not limited to implementations that solve any or all of the disadvantages mentioned in the background technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to be able to understand the features of the present invention, the present invention may be described in detail with reference to certain embodiments, some of which are illustrated in the accompanying drawings. However, it should be noted that the accompanying drawings illustrate only certain embodiments of the present invention and should not be considered as limiting the scope thereof, as the scope of the present invention encompasses other equivalent embodiments. The accompanying drawings are not necessarily to scale, and emphasis is generally placed on illustrating the features of certain embodiments of the present invention. In the accompanying drawings, the same reference numerals are used to indicate the same parts in the various views. Therefore, in order to further understand the present invention, reference may be made to the following detailed description, read in conjunction with the accompanying drawings, wherein:
[0015] Figures 1A to 1D is an exemplary process for a soluble bonding layer in a caustic bath according to one aspect;
[0016] Figure 2 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0017] Figure 3 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0018] Figure 4 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0019] Figure 5 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0020] Figure 6 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0021] Figure 7 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0022] Figure 8 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0023] Fig. 9 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0024] Fig.10 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0025] Fig.11 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect;
[0026] Fig.12 is a cross-sectional view of a multilayer film containing a soluble tie layer according to one aspect; and
[0027] Fig.13 is a schematic diagram of a hot blown film process for preparing a multilayer film according to one aspect. DETAILED DESCRIPTION
[0028] As used herein, the term "film" includes plastic mesh, regardless of whether it is a film or a sheet. The thickness of the film can be 0.25 mm or less, or a thickness of 0.35-30 mils, or 0.5-25 mils, or 0.5-15 mils, or 1-10 mils, or 1-8 mils, or 1.1-7 mils, or 1.2-6 mils, or 1.3-5 mils, or 1.5-4 mils, or 1.6-3.5 mils, or 1.8-3.3 mils, or 2-3 mils, or 1.5-4 mils, or 0.5-1.5 mils, or 1-1.5 mils, or 0.7-1.3 mils, or 0.8-1.2 mils, or 0.9-1.1 mils.
[0029] The multilayer film described herein includes at least one soluble adhesive layer, the soluble adhesive layer is bonded to two layers of the multilayer film, and its bonding strength is at least 2.5 N / 15mm, 3.0 N / 15mm, 3.5 N / 15mm, 4.0 N / 15mm, 4.5 N / 15mm or 5.0 N / 15mm according to ASTM F904. At an elevated temperature, within 30, 25, 20 or 15 minutes, at least 90% (and in some embodiments at least 95%) of the soluble adhesive layer dissipates from the adjacent layer by separation and / or dissolution in a caustic solution containing 1% by weight of sodium hydroxide. The elevated temperature is 45°C, 55°C, 65°C, 75°C, 85°C, 95°C, and the multilayer film is prepared according to APR Tensile Test Standard PET-P-00 issued on April 11, 2019, the contents of which are incorporated herein by reference. The remaining test parameters are according to APR draw-down test standard PET-P-00 published on April 11, 2019. The multilayer film may further include additional layers, for example to increase bulk, provide functionality, barrier, resistance to mechanical damage, printability or serve as an additional tie layer.
[0030] Once placed in a caustic wash solution, the soluble bonding layer allows the layers of the membrane to separate. This helps with the recyclability and reuse of the different layers of the membrane. For example, insoluble layers will remain as solids. Depending on buoyancy, some solids may sink or float, allowing further separation of the materials. The soluble materials can then be precipitated from the caustic solution.
[0031] The multilayer films described herein may comprise at least and / or at most any of the following number of layers: 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, and 15. As used herein, the term "layer" refers to a discrete film component that is substantially coextensive with the film and has a substantially uniform composition. In the case where two or more directly adjacent layers have substantially the same composition, then for the purposes of this application, the two or more adjacent layers may be considered a single layer. In an embodiment, the multilayer film utilizes microlayers to form a single layer. The microlayer portion may include between 10-1,000 microlayers in each microlayer portion. In an embodiment, one or more layers of the multilayer film may be a printing layer. In an embodiment, the printing layer is an ink soluble in a caustic washing solution.
[0032] Below are some non-limiting examples of combinations, where letter symbols designate film layers. Where the following multilayer film representation includes the same letter more than once, each occurrence of the letter may represent the same composition or a different composition within a category that performs a similar function. It should be understood that each letter may represent multiple layers within a category that performs a similar function. It should further be understood that additional layers (e.g., bulk layers) are not described below, but are intended.
[0033] A / C / A, A / C / B / A, A / C / D / A, A / C / B / C / A, A / C / B / D / A, A / B / C / D / A, A / B / D / C / A, A / B / C / B / A, A / C / D / C / A, A / D / C / D / A, A / B / C / B / D / A, A / B / C / B / C / A, A / B / C / D / B / A, A / B / C / D / C / A, A / B / D / B / C / A, A / B / D / C / B / A, A / B / D / C / D / A, A / C / B / C / B / A, A / C / B / C / D / A, A / C / B / D / B / A, A / C / B / D / C / A, A / C / D / B / D / A, A / C / D / C / B / A, A / D / C / B / D / A, A / D / B / D / C / A, A / B / C / D / B / D / A, A / B / D / C / B / D / A, A / B / D / C / B / C / A, A / C / B / C / B / D / A, A / C / B / C / B / C / A, A / C / B / D / B / D / A, A / C / B / C / D / C / A, A / D / C / B / C / D / A, A / C / B / C / B / D / C / A, A / C / B / C / B / C / D / A, A / C / B / D / B / D / C / A, A / C / D / C / B / C / D / A, A / B / C / D / B / C / D / A, A / D / C / B / C / B / C / A, A / D / C / B / D / B / C / A, A / D / C / B / C / B / D / A.
[0034] "A" represents the outer layer, as discussed herein.
[0035] "B" denotes an inner layer including a barrier layer, as discussed herein.
[0036] "C" represents a soluble bonding layer, as discussed herein.
[0037] "D" represents an adhesive tie layer, as discussed herein.
[0038] Unless otherwise indicated, all composition percentages used herein are presented on a "by weight" basis.
[0039] Turning now to the multilayer film structure, the film structure comprises two outer layers and at least one soluble tie layer. In an embodiment, the multilayer film structure further comprises at least one adhesive tie layer and / or at least one inner layer. The multilayer film is a polymer structure formed by coextrusion, extrusion coating, coating, lamination or extrusion lamination.
[0040] "Outer layer" refers to a surface layer or skin layer, generally the outermost layer, typically of a multilayer film, but additional layers, coatings and / or films may also be adhered thereto. In an embodiment, both outer layers are polyester outer layers comprising polyester and / or copolyester as a major component. In an embodiment, the polyester and polyester copolymers constitute 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9% by weight, or substantially all of one or both outer layers. In an embodiment, the polyester is polyethylene terephthalate or recycled polyethylene terephthalate.
[0041] In other embodiments, at least one of the outer layers is polyethylene, in embodiments, at least one of the outer layers is ethylene / alpha-olefin copolymer. In embodiments, ethylene / alpha-olefin copolymer constitutes 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9% by weight, or substantially all of one or both outer layers.
[0042] In other embodiments, at least one of the outer layers is a polyamide. In embodiments, the polyamide is selected from polyamide 6, polyamide 6 / 66, polyamide 6 / 6, amorphous polyamide (e.g., 6I / 6T). In embodiments, the polyamide constitutes 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9% by weight, or substantially all of one or both outer layers.
[0043] In an embodiment, at least one of the outer layer is a heat seal layer. Heat seal refers to any seal of the first area of the film surface and the second area of the film surface, wherein a seal is formed by heating the area to at least their respective sealing starting temperature. Heat seal is a process for joining two or more thermoplastic films or sheets by heating the areas in contact with each other to a temperature (usually by means of pressure) where melting occurs. Heating can be carried out in any one or more ways, such as using a heating rod, a hot wire, hot air, infrared radiation, ultraviolet radiation, an electron beam, ultrasound, induction and a molten bead. Heat seal is a relatively narrow seal (for example, 0.02 inch to 1 inch wide) across the film typically. A special heat seal device is a heat seal performed using an impulse sealer, which uses a combination of heat and pressure to form a seal, wherein a heating device provides a short-lived heat pulse while applying pressure to the film by a sealing rod or a sealing wire, and then rapidly cools the rod or wire.
[0044] Heat seal layer comprises thermoplastic polymer, includes but not limited to thermoplastic polyolefin, polyamide, polyester and polyvinyl chloride.In embodiment, the polymer for sealant layer comprises homogeneous ethylene / alpha-olefin copolymer, heterogeneous ethylene / alpha-olefin copolymer, ethylene homopolymer and ethylene / vinyl acetate copolymer.In some embodiments, heat seal layer can comprise polyolefin, particularly ethylene / alpha-olefin copolymer.For example, density is 0.88 g / cc to 0.917 g / cc or 0.90 g / cc to 0.917 g / cc or less than the polyolefin of 0.92 g / cc.More particularly, seal layer can comprise at least one selected from high density polyethylene, linear low density polyethylene, medium density polyethylene, low density polyethylene, very low density polyethylene, homogeneous ethylene / alpha-olefin copolymer, polypropylene and polypropylene copolymer.“Polymer” refers to homopolymer, copolymer, terpolymer etc. in this article.“Copolymer” includes copolymer, terpolymer etc. in this article.
[0045] In an embodiment, the melting point of the heat seal layer is less than any of the following values: 220°C, 210°C, 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 140°C, and 130°C; and the melting point of the heat seal layer may be at least any of the following values: 65°C, 70°C, 75°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C. In an embodiment, the heat seal layer comprises 80-99% by weight of a linear low density polyethylene copolymer having a melting point between 90-130°C. In an embodiment, the heat seal layer comprises 80-99% by weight of a very low density polyethylene copolymer having a melting point between 65-125°C. All references to the melting point of a polymer, resin, or film layer in this application refer to the melting peak temperature of the main melting phase of the polymer, resin, or layer as determined by differential scanning calorimetry according to ASTM D-3418.
[0046] In embodiments where the heat seal layer comprises an amorphous material, then the heat seal layer may not clearly show a melting point. The glass transition temperature of the heat seal layer may be less than any of the following values, and may vary between any of the following values: 125°C, 120°C, 110°C, 100°C, 90°C, 80°C, 70°C, 60°C, and 50°C; the measured relative humidity may be any of the following values: 100%, 75%, 50%, 25%, and 0%. All references to the glass transition temperature (Tg) of a polymer are determined using ASTM D3418 "Standard Test Method for Determination of Transition Temperature of Polymers by Thermal Analysis" determined by the PerkinElmer "Half Cp Extrapolation" (the "Half Cp Extrapolation" reports the point on the curve where the change in specific heat is half of the change in a complete transition), which is incorporated herein by reference in its entirety.
[0047] In an embodiment, at least one of the outer layers is an abuse layer.The main function of the abuse layer is to provide puncture resistance, mechanical damage resistance and abrasion resistance.
[0048] The thickness of the outer layer can be selected to provide enough materials to affect the strong heat seal combination, or provide resistance to mechanical damage, but it can not be too thick to negatively affect the characteristics of the film to an unacceptable level. The thickness of the outer layer can be at least any one of the following values: 0.05 mil, 0.1 mil, 0.15 mil, 0.2 mil, 0.25 mil, 0.3 mil, 0.35 mil, 0.4 mil, 0.45 mil, 0.5 mil and 0.6 mil. The thickness of the outer layer can be less than any one of the following values: 5 mils, 4 mils, 3 mils, 2 mils, 1 mil, 0.7 mil, 0.5 mil and 0.3 mil. The thickness of the outer layer accounts for the percentage of the total thickness of the film and can be less than any one of the following values: 50%, 40%, 30%, 25%, 20%, 15%, 10% and 5%; and can change (for example, 10% to 30%) between any of the above values.
[0049] The multilayer film includes a soluble adhesive layer as the inner layer of the multilayer film. The soluble adhesive layer is bonded to two other layers of the multilayer film. At elevated temperatures, within 30, 25, 20 or 15 minutes, at least 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.2% or substantially all of the soluble adhesive layer dissipates from the adjacent layers by separation and / or dissolution in a caustic solution containing 1% by weight of sodium hydroxide. The elevated temperature is 45°C, 55°C, 65°C, 75°C, 85°C, 95°C, and the multilayer film is prepared according to the APR tensile test standard PET-P-00 issued on April 11, 2019. The remaining test parameters are according to the APR tensile test standard PET-P-00 issued on April 11, 2019. It should be understood that although these parameters relate to samples containing PET, samples without PET can be tested.
[0050] In an embodiment, the soluble tie layer can be extrusion coated, coated and / or coextruded with an outer layer. In an embodiment, the soluble tie layer is bonded to a polyethylene or PET outer layer on one side and to at least one other layer on the other side with sufficient interlayer bond strength to prevent adhesive failure. In an embodiment, the other layer is a barrier layer as described herein.
[0051] The term "bond strength" as used herein refers to the force required to separate or delaminate the films at adjacent film layers by adhesive failure or the force required to cause cohesive failure within adjacent layers, plus the amount of force to bend the layers during the test, as measured in accordance with ASTM F904 using an Instron tensile tester crosshead speed of 10 inches / minute and five 1 inch wide representative specimens while supporting the unseparated portion of each test specimen at 90° to the direction of pull. "Adhesive failure" is a failure in which the interfacial forces holding the two surfaces together (e.g., valence forces or interlocking effects or both) are overcome.
[0052] The minimum bond strength of the film is the weakest bond strength indicated from the separation test of the layers of the film. The minimum bond strength indicates the internal strength at which the film remains intact to be used as a single unit. The bond strength is provided by the interlayer adhesion (i.e., interlayer adhesive bond strength) and the intralayer cohesion of each film layer (i.e., intralayer cohesive strength).
[0053] As used herein, "adhesive failure" refers to a failure in which the interfacial forces (eg, valence forces or interlocking effects or both) holding two surfaces together are overcome. "Cohesive failure" is a failure in which the molecular attractions holding the layer components together are overcome.
[0054] The minimum bonding strength of the soluble adhesive layer to the adjacent layers can be at least about any of the following: 2.5 N / 15mm, 3.0 N / 15mm, 3.5 N / 15mm, 4.0 N / 15mm, 4.5 N / 15mm, 5.0 N / 15mm, 6.0 N / 15mm, 7.0 N / 15mm, 8.0 N / 15mm, 9.0 N / 15mm, 10.0 N / 15mm, 11.0 N / 15mm or 12.0 N / 15mm. According to ASTM F904, the minimum bonding strength between each of the adjacent layers of the plurality of layers of the film can be at least about any of the values in the preceding sentence.
[0055] The soluble tie layer is made of a material that can be coextruded with the other layers of the multilayer film. For example, the soluble tie layer can be processed at a temperature required during the extrusion of the other layers of the multilayer film. The temperature is typically in excess of 200°C, 225°C, 250°C, 275°C or 300°C.
[0056] The soluble bonding layer comprises at least 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, 90 wt% or 100 wt% of ethylene acrylic acid copolymer, ethylene methacrylic acid copolymer or a blend thereof, wherein 20-90%, 30-80% or 40-70% of the acid moieties are neutralized by adding KOH or NaOH. In an embodiment, at least 50%, 55%, 60%, 65% or 70% of the acid moieties of the ethylene acrylic acid copolymer, ethylene methacrylic acid copolymer or a blend thereof are neutralized. In an embodiment, the acid moieties are neutralized by adding KOH. In an embodiment, the acid moieties are neutralized by adding NaOH. In an embodiment, the ethylene acrylic acid copolymer, ethylene methacrylic acid copolymer or a blend thereof in the soluble bonding comprises 0.1%-4.0% maleic anhydride grafting.
[0057] In embodiments, the soluble tie layer further comprises up to 30%, 20%, 10%, or 5% by weight of modified LLDPE, ethylene methyl acrylate, or ethylene methacrylic acid. In embodiments, the soluble tie layer further comprises up to 30%, 20%, 10%, or 5% by weight of a sulfopolyester. Exemplary sulfopolyesters include, but are not limited to, AQ SULFATE available from Eastman Chemical. tm In embodiments, the soluble tie layer further comprises up to 40%, 30%, 20%, 10%, or 5% by weight of a polyamide derived from a dimer fatty acid and a diamine. Exemplary polyamides include, but are not limited to, Uni-Rez available from Kraton. tm and Versamid available from Gabriel ®. In embodiments, the soluble adhesive layer further comprises up to 40 wt%, 30 wt%, 20 wt%, 10 wt% or 5 wt% of a caustic soluble rosin modifier. Suitable rosin modifiers include, but are not limited to, gum rosin, wood rosin, tall oil rosin, hydrogenated rosin and other rosin derivatives soluble or dispersible in caustic solutions as described herein. In embodiments, the soluble adhesive layer further comprises up to 10 wt%, 9 wt%, 8 wt%, 7 wt%, 6 wt%, 5 wt%, 4 wt%, 3 wt%, 2 wt% or 1 wt% of a plasticizer or surfactant. In embodiments, the plasticizer or surfactant comprises glycerol, triacetin, citric acid ester, ethoxylated fatty alcohol, sorbitan ester, ethoxylated sorbitan ester, fatty acid, fatty acid monoglyceride and fatty acid diglyceride and blends thereof. In embodiments, the plasticizer and surfactant used for the soluble adhesive layer are soluble or dispersible in a caustic bath. In an embodiment, the soluble adhesive layer further comprises an effective amount of an antioxidant, such as 0.5-1.5 wt %. The antioxidant may be included in the masterbatch and may further contain a primary antioxidant and a secondary antioxidant. The soluble adhesive layer may contain some or all of the components described in this paragraph. The combination of components is soluble or dispersible in a caustic solution so that at elevated temperatures, within 30, 25, 20 or 15 minutes, at least 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.2% or substantially all of the soluble adhesive layer dissipates from adjacent layers by separation, dissolution or dispersion in a caustic solution containing 1 wt % sodium hydroxide. The elevated temperature is 45°C, 55°C, 65°C, 75°C, 85°C, 95°C, and the multilayer film is prepared according to the APR draft test standard PET-P-00 issued on April 11, 2019. The remaining test parameters are based on the APR tensile test standard PET-P-00 published on April 11, 2019.
[0058] In one embodiment, the soluble tie layer comprises up to 30% modified LLDPE, ethylene methyl acrylate or ethylene methacrylic acid; between 10% to 90%, 20% to 80%, or 30% to 70% by weight of ethylene acrylic acid copolymer (20-90% of which has been neutralized by the addition of KOH or NaOH); up to 30% sulfopolyester; up to 20% caustic soluble rosin modifier and up to 10% plasticizer.
[0059] In another embodiment, the soluble bonding layer comprises 15-60% ethylene acrylic acid copolymer (20-90% neutralized by addition of KOH or NaOH), 20-40% hydrogenated wood rosin, 2-10% ethoxylated sorbitan monostearate, and 25-50% polyamide derived from dimer fatty acid and diamine.
[0060] In another embodiment, the soluble tie layer comprises between 40% to 90%, 50% to 80% or 60% to 70% by weight of ethylene acrylic acid copolymer (20-90% of which has been neutralized by the addition of KOH or NaOH); up to 30% of sulfopolyester; up to 20% of a caustic soluble rosin modifier and up to 10% of a plasticizer.
[0061] In embodiments, the soluble tie layer has a melt index or composite melt index of at least 0.3, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, or 10 g / 10 min at 190°C and 2.16 kg as measured according to ASTM D1238.
[0062] The thickness of the soluble adhesive layer can be at least any one of the following values: 0.05 mil, 0.1 mil, 0.15 mil, 0.2 mil, 0.25 mil, 0.3 mil, 0.35 mil, 0.4 mil, 0.45 mil, 0.5 mil and 0.6 mil. The thickness of the outer layer can be less than any one of the following values: 5 mil, 4 mil, 3 mil, 2 mil, 1 mil, 0.7 mil, 0.5 mil and 0.3 mil. The thickness of the soluble adhesive layer accounts for the percentage of the total thickness of the film and can be less than any one of the following values: 50%, 40%, 30%, 25%, 20%, 15%, 10% and 5%; and can change (e.g., 10% to 30%) between any of the above values.
[0063] In embodiments, the multilayer film includes at least one adhesive bonding layer. The adhesive bonding layer refers to the internal film layer that two layers are adhered to each other. Useful adhesive bonding polymers include thermoplastic polymers, which can be compatible with the polymer of a directly adjacent layer and the polymer of another directly adjacent layer. Such dual compatibility enhances the adhesion of the layers of bonding to each other. The adhesive bonding layer can be made of polyolefin, such as modified polyolefin, ethylene / vinyl acetate copolymer, modified ethylene / vinyl acetate copolymer, ethylene / methyl acrylate copolymer, modified ethylene / methyl acrylate copolymer and homogeneous ethylene / alpha-olefin copolymer. Typical adhesive layer polyolefin includes anhydride-modified grafted linear low-density polyethylene, anhydride-grafted (i.e. anhydride-modified) low-density polyethylene, anhydride-grafted polypropylene, anhydride-grafted methyl acrylate copolymer, anhydride-grafted butyl acrylate copolymer, homogeneous ethylene / alpha-olefin copolymer and anhydride-grafted ethylene / vinyl acetate copolymer. The adhesive bonding layer can include copolyester, PET copolyester or its blend. In embodiments, the adhesive tie layer includes at least 0.5, 1.0, 1.5, 2.0, 2.5, or 3.0 weight percent of a polymer found in an adjacent layer.
[0064] The thickness of the adhesive bonding layer can be any one of at least the following values: 0.05 mil, 0.1 mil, 0.15 mil, 0.2 mil, 0.25 mil, 0.3 mil, 0.35 mil, 0.4 mil, 0.45 mil, 0.5 mil and 0.6 mil. The thickness of the outer layer can be less than any one of the following values: 5 mils, 4 mils, 3 mils, 2 mils, 1 mil, 0.7 mil, 0.5 mil and 0.3 mil. The thickness of the adhesive bonding layer accounts for the percentage of the total thickness of the film and can be less than any one of the following values: 20%, 17%, 15%, 12%, 10%, 8%, 5% and 3%; and can change (for example, 5% to 20%) between any of the above values.
[0065] An inner layer refers to a film layer that is not an outer layer or surface layer. An inner layer is between two outer layers and may be in direct contact with the outer layers, or there may be another layer between the inner layer and the outer layer.
[0066] In embodiments having multiple inner layers, the composition, thickness, and other properties of the second inner layer may be substantially the same as any of those of the first inner layer, or may be different from any of those of the first inner layer.
[0067] The multilayer film may further include at least one barrier layer. As used herein, the term "barrier" and the phrase "barrier layer" when applied to a film and / or a film layer are used with respect to the ability of the film or film layer to act as a barrier to one or more gases. Oxygen transmission rate is a method of quantifying the effect of a barrier layer. As used herein, the term "oxygen transmission rate" refers to the oxygen that permeates a film according to ASTM D3985 "Standard Test Method for Oxygen Transmission Rate Through Plastic Film and Sheeting Using a Coulometric Sensor", which is incorporated herein by reference in its entirety.
[0068] Useful barrier polymers include vinylidene chloride polymers ("PVdC"), ethylene / vinyl alcohol copolymers ("EVOH"), polyvinyl alcohol copolymers ("PVOH"), thermoplastic starch, polyesters and / or polyamides.
[0069] Vinylidene chloride polymers ("PVdC") are polymers or copolymers containing vinylidene chloride, i.e., polymers comprising at least 50% by weight of monomer units derived from vinylidene chloride (CH2=CC12). PVdC optionally comprises C1-C1 derivatives derived from vinyl chloride, styrene, vinyl acetate, acrylonitrile and (meth) acrylic acid. 12The monomer units of one or more of the alkyl esters (e.g., methyl acrylate, butyl acrylate, methyl methacrylate). As used herein, "(meth)acrylic acid" refers to both acrylic acid and / or methacrylic acid; and "(meth)acrylate" refers to both acrylate and methacrylate. Examples of PVdC include one or more of the following: vinylidene chloride homopolymer, vinylidene chloride / vinyl chloride copolymer ("VDC / VC"), vinylidene chloride / methyl acrylate copolymer ("VDC / MA"), vinylidene chloride / ethyl acrylate copolymer, vinylidene chloride / ethyl methacrylate copolymer, vinylidene chloride / methyl methacrylate copolymer, vinylidene chloride / butyl acrylate copolymer, vinylidene chloride / styrene copolymer, vinylidene chloride / acrylonitrile copolymer, and vinylidene chloride / vinyl acetate copolymer.
[0070] Useful PVdCs include those having at least about 75 wt%, up to about 95 wt%, and up to about 98 wt% vinylidene chloride monomer. Useful PVdCs (e.g., as applied by latex emulsion coating) include those having at least about 5%, 10%, and 15% and / or up to about 25%, 22%, 20%, and 15% comonomer and vinylidene chloride monomer.
[0071] Useful PVdCs include weight average molecular weight (M w ) is at least about any of the following: 10,000; 50,000; 80,000; 90,000; 100,000; 111,000; 120,000; 150,000; and 180,000; and up to about any of the following: 180,000; 170,000; 160,000; 150,000; 140,000; 100,000; and 50,000. Useful PVdCs also include viscosity average molecular weight (M z ) is at least about any of the following: 130,000; 150,000; 170,000; 200,000; 250,000; and 300,000; and at most about any of the following: 300,000; 270,000; 250,000; and 240,000.
[0072] Barrier layers comprising PVdC may also include thermal stabilizers (eg, hydrogen chloride scavengers such as epoxidized soybean oil) and lubricating processing aids (eg, one or more polyacrylates).
[0073] Ethylene / vinyl alcohol copolymer ("EVOH") is another useful barrier polymer. The ethylene content of EVOH can be about 32%, or at least about any of the following values: 20%, 25%, 30%, and 38% by weight. The ethylene content of EVOH can be up to about any of the following values: 50%, 48%, 40%, 35%, and 33% by weight. EVOH can include saponified or hydrolyzed ethylene / vinyl acetate copolymers, such as those having a degree of hydrolysis of at least about any of the following values: 50%, 85%, 90%, 95%. The ethylene content of EVOH can range from about 20 mol% to about 44 mol%. Exemplary EVOH is commercially available from Evalca Corporation with ethylene contents of 29, 32, 35, 38, and 44 mol%.
[0074] Polyvinyl alcohol copolymer ("PVOH") is another useful barrier polymer. For example, PVOH is at least 95% hydrolyzed.
[0075] Thermoplastic starches which are high amylose and modified starches derived from wheat, corn, potato, rice, oat, arrowroot or pea sources are also useful barrier materials. Starches modified by reaction with hydroxyalkyl, acetate or dicarboxylic anhydrides or grafted polymers are also useful.
[0076] Certain polyamides are known to provide barrier properties. Such polyamides include, but are not limited to, polycaprolactam (nylon 6), meta-xylylene adipamide (MXD6), hexamethylene adipamide (nylon 66), amorphous polyamides (eg, nylon 6I, 6T), and various copolymers and various blends of the above amides.
[0077] Certain polyesters further provide barrier properties. Polyesters are homopolymers or copolymers having ester bonds between monomer units, which can be formed, for example, by a polycondensation reaction between a dicarboxylic acid and a diol. Suitable polyesters include poly(ethylene 2,6-naphthalate), poly(butylene terephthalate), poly(ethylene terephthalate), poly(ethylene furanoate), and copolyesters obtained by reacting one or more aromatic dicarboxylic acids with one or more dihydric alcohols, such as PETG, which is an amorphous copolyester of terephthalic acid with ethylene glycol and 1,4-cyclohexanedimethanol.
[0078] The barrier layer may comprise one or more barrier polymers in an amount of at least about any of the following: 50%, 60%, 70%, 80%, 90%, 95% and 100%; and / or at most about any of the following: 60%, 70%, 80%, 90% and 95%, based on the weight of the barrier layer. In some embodiments, the barrier polymer is selected from any one or more of EVOH, PVOH, polyester, thermoplastic starch, PVdC and polyamide. In other embodiments, the barrier layer is a polyester coated with PVdC, silicon oxide or aluminum oxide.
[0079] In embodiments containing a barrier layer, the additional inner layer may be, for example, between the outer layer and the barrier layer. The additional inner layer may be directly adjacent to the outer layer, such that there is no intermediate layer between the additional inner layer and the outer layer. The additional inner layer may be directly adjacent to the barrier layer, such that there is no intermediate layer between the additional inner layer and the barrier layer. The additional inner layer may be directly adjacent to both the outer layer and the barrier layer.
[0080] The thickness of the inner layer can be at least about and / or at most about any of the following: 0.05, 0.1, 0.15, 0.2, 0.25, 0.5, 1, 2, 3, 4, and 5 mils. If used as a barrier layer, the thickness and composition of the barrier layer can be sufficient to impart the oxygen permeability of the film containing the barrier layer as listed herein. The thickness of the inner layer as a percentage of the total thickness of the film can be at least about and / or at most about any of the following: 1, 3, 5, 7, 10, 15, 20, 25, 30, 35, 40, 45, and 50%.
[0081] The inner layer can be a functional layer or a main layer. The main layer is generally one or more layers of film, which can increase the mechanical damage resistance, toughness or modulus of the film, or simply increase the thickness, and can include recycled content. In some embodiments, the film comprises a main layer, which is used to increase the mechanical damage resistance, toughness and / or modulus of the film. The main layer generally comprises a polymer that is cheaper than other polymers in the film, and the other polymers provide some specific purposes unrelated to mechanical damage resistance, modulus, etc. In an embodiment, the main layer comprises at least one selected from the following: ethylene / alpha-olefin copolymers, ethylene homopolymers, propylene / alpha-olefin copolymers, propylene homopolymers, propylene copolymers and combinations thereof.
[0082] As used herein, the term "polyolefin" refers to olefin polymers and copolymers, especially ethylene and propylene polymers and copolymers, and polymer materials with at least one olefin comonomer. Polyolefins can be linear, branched, cyclic, aliphatic, aromatic, substituted or unsubstituted. The term polyolefin includes copolymers of homopolymers of olefins, copolymers of olefins, olefins and non-olefin comonomers (such as vinyl monomers, acrylic acid, modified polymers of the above monomers, etc.) that can be copolymerized with olefins. Modified polyolefins include modified polymers prepared by copolymerization or grafting of homopolymers of olefins or their copolymers with unsaturated carboxylic acids (such as maleic acid, fumaric acid, etc.) or their derivatives (such as anhydrides, esters, metal salts, etc. of carboxylic acids). It can also be obtained by introducing unsaturated carboxylic acids (such as maleic acid, fumaric acid, etc.) or their derivatives (such as anhydrides, esters, metal salts, etc. of carboxylic acids) into olefin homopolymers or copolymers. In an embodiment, the heat seal layer is mainly composed of polyolefins. In an embodiment, based on the total composition of the heat seal layer, the total polyolefin content of the heat seal layer is 90-99% by weight.
[0083] Ethylene homopolymer or copolymer refers to ethylene homopolymers, such as low density polyethylene, medium density polyethylene, high density polyethylene; ethylene / alpha olefin copolymers, such as those defined below; and other ethylene copolymers, such as ethylene / vinyl acetate copolymers; ethylene / alkyl acrylate copolymers; or ethylene / (meth)acrylic acid copolymers. Ethylene / alpha-olefin copolymers herein refer to ethylene and one or more selected from C4-C 10 Copolymers of comonomers of α-olefins (e.g., 1-butene, 1-hexene, 1-octene, etc.), wherein the molecules of the copolymers comprise long polymer chains having relatively few side chain branches from the α-olefins reacted with ethylene. This molecular structure contrasts with conventional high-pressure low-density or medium-density polyethylene, which is highly branched relative to ethylene / α-olefin copolymers, and the high-pressure polyethylene contains both long-chain branching and short-chain branching. Ethylene / α-olefin copolymers include one or more of the following: 1) high-density polyethylene, e.g., a density greater than 0.94 g / cm 3 , 2) medium density polyethylene, for example, with a density of 0.93-0.94 g / cm 3 , 3) Linear medium density polyethylene, for example, with a density of 0.926-0.94 gg / cm 3 , 4) low density polyethylene, for example, with a density of 0.915-0.939 g / cm 3 , 5) Linear low density polyethylene, for example, with a density of 0.915-0.935 g / cm 3 , 6) Very low or ultra-low density polyethylene, for example, with a density below 0.915 g / cm 3, and homogeneous ethylene / α-olefin copolymers. Homogeneous ethylene / α-olefin copolymers include those having a density less than about any of the following: 0.925, 0.922, 0.92, 0.917, 0.915, 0.912, 0.91, 0.907, 0.905, 0.903, 0.90, and 0.86 g / cm 3 Unless otherwise indicated, all densities herein are measured according to ASTM D1505.
[0084] "Polyamide" herein refers to polymers having amide bonds along the molecular chain, and preferably synthetic polyamides, such as nylon. In addition, such term encompasses polymers comprising repeating units derived from monomers (such as caprolactam, which is polymerized to form polyamides) and both polymers of diamines and diacids, and copolymers of two or more amide monomers, including nylon terpolymers, sometimes referred to in the art as "copolyamides." “Polyamide” specifically includes those aliphatic polyamides or copolyamides commonly referred to as, for example, polyamide 6 (homopolymer based on ε-caprolactam), polyamide 69 (homocondensation polymer based on hexamethylenediamine and azelaic acid), polyamide 610 (homocondensation polymer based on hexamethylenediamine and sebacic acid), polyamide 612 (homocondensation polymer based on hexamethylenediamine and dodecanedioic acid), polyamide 11 (homopolymer based on 11-aminoundecanoic acid), polyamide 12 (homopolymer based on ω-aminododecanoic acid or based on laurolactam), polyamide 6 / 12 (polyamide copolymer based on ε-caprolactam and laurolactam), polyamide 6 / 66 (polyamide copolymer based on ε-caprolactam and hexamethylenediamine and adipic acid), polyamide 66 / 610 (polyamide copolymer based on hexamethylenediamine, adipic acid and sebacic acid), modifications thereof, and blends thereof. Polyamides also include crystalline or partially crystalline, amorphous (6I / 6T), aromatic or partially aromatic polyamides.
[0085] As used herein, "polyester" includes polymers prepared by 1) condensation of polyfunctional carboxylic acids with polyfunctional alcohols, 2) polycondensation of hydroxycarboxylic acids, and 3) ring-opening polymerization of cyclic esters (eg, lactones).
[0086] Exemplary multifunctional carboxylic acids (including their derivatives, such as anhydrides or simple esters, such as methyl esters) include aromatic dicarboxylic acids and derivatives (e.g., terephthalic acid, isophthalic acid, dimethyl terephthalate, dimethyl isophthalate, 2,5-furandicarboxylic acid, naphthalene-2,6-dicarboxylic acid); and aliphatic dicarboxylic acids and derivatives (e.g., adipic acid, azelaic acid, sebacic acid, oxalic acid, succinic acid, glutaric acid, dodecanedioic acid, 1,4-cyclohexanedicarboxylic acid, dimethyl-1,4-cyclohexanedicarboxylate, dimethyl adipate). Representative dicarboxylic acids can be represented by the following general formula:
[0087] HOOC--Z--COOH
[0088] Wherein Z represents a divalent aliphatic group containing at least 2 carbon atoms. Representative examples include adipic acid, sebacic acid, octadecanedioic acid, pimelic acid, suberic acid, azelaic acid, dodecanedioic acid and glutaric acid. The dicarboxylic acid can be an aliphatic acid, or an aromatic acid, such as isophthalic acid ("I") and terephthalic acid ("T"). As known to those skilled in the art, polyesters can be produced using anhydrides and esters of multifunctional carboxylic acids.
[0089] Exemplary polyfunctional alcohols include diols (and bisphenols) such as ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,4-cyclohexanedimethanol, 2,2-dimethyl-1,3-propanediol, 1,6-hexanediol, poly(tetrahydroxy-1,1'-biphenyl, 1,4-hydroquinone, bisphenol A, and cyclohexanedimethanol ("CHDM").
[0090] Exemplary hydroxycarboxylic acids and lactones include 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, pivalolactone, and caprolactone.
[0091] Exemplary polyesters include polyethylene terephthalate or recycled polyethylene terephthalate.Exemplary polyesters may be derived from lactone polymerization; these include, for example, polycaprolactone and polylactic acid.
[0092] The polyester may include or be a modified polyester. Exemplary modified polyesters include glycol-modified polyesters and acid-modified polyesters. The modified polyesters are prepared by polymerization with more than one type of comonomer to destroy crystallinity and thus make the resulting polyester more amorphous.
[0093] Glycol-modified polyesters are polyesters obtained by condensing at least one polyfunctional carboxylic acid with at least two types of polyfunctional alcohols. For example, glycol-modified poly(ethylene terephthalate) or "PETG" can be prepared by condensing terephthalic acid with ethylene glycol and cyclohexanedimethanol ("CHDM"). Useful PETG is available from Eastman Corporation under the trade name Eastar 6763 and is believed to have a CHDM monomer content of about 34 mole %, an ethylene glycol monomer content of about 16 mole %, and a terephthalic acid monomer content of about 50 mole %. Another useful glycol-modified polyester can be prepared similarly to PETG, but with dimethyl terephthalate instead of the terephthalic acid component. Another exemplary glycol-modified polyester is available from Eastman Corporation under the trade designation Ecdel 9965 and is believed to have a density of 1.13 g / cc and a melting point of 195° C. and is derived from dimethyl 1,4-cyclohexanedicarboxylate, 1,4-cyclohexanedimethanol, and poly(tetramethylene ether glycol).
[0094] Exemplary acid-modified polyesters can be prepared by condensation of at least one polyfunctional alcohol with at least two types of polyfunctional carboxylic acids. For example, at least one of the polyfunctional alcohols listed above can be condensed with two or more of the polyfunctional carboxylic acids listed above (e.g., isophthalic acid, adipic acid, and / or naphthalene-2,6-dicarboxylic acid). Exemplary acid-modified polyesters can be derived from about 5 mole % isophthalic acid, about 45 mole % terephthalic acid, and about 50 mole % ethylene glycol, such as those available from Invista Corporation.
[0095] The polyester may be selected from randomly polymerized polyesters or block polymerized polyesters.
[0096] The polyester may be derived from one or more of any of the ingredients discussed above. If the polyester includes mer units derived from terephthalic acid, the diacid of the polyester may contain at least about any of 70, 75, 80, 85, 90, and 95% such mer content (mol%).
[0097] The polyester can be thermoplastic. The polyester can be substantially amorphous, or can be partially crystalline (semi-crystalline). The crystallinity of the polyester and / or the skin layer can be at least about and / or at most about any of the following weight percentages: 5, 10, 15, 20, 25, 30, 35, 40, and 50%.
[0098] Crystallinity can be determined indirectly by thermal analysis methods, which use the heat of fusion measurement performed by differential scanning calorimetry ("DSC"). Unless otherwise stated, the percentage crystallinity of all polymers, polymer mixtures, resins, films or layers mentioned in this application is performed by DSC thermal analysis methods. DSC thermal analysis methods are considered to be the most widely used methods for estimating polymer crystallinity, and therefore suitable procedures are known to those skilled in the art. For example, see "Crystallinity Determination," Encyclopedia of Polymer Science and Engineering, Vol. 4, pp. 482-520 (John Wiley & Sons, 1986), which is incorporated herein by reference in its 482-520 pages.
[0099] According to the DSC thermal analysis method, the weight fraction of crystallinity (i.e., "crystallinity" or "Wc") is defined as ΔHP / AHf,c, where "ΔHP" is the measured heat of fusion of the sample (i.e., the area under the heat flow of the sample relative to the temperature curve), and "AHf,c" is the theoretical heat of fusion of a 100% crystalline sample. AHf,c values for many polymers have been obtained by extrapolation methods; for example, see Table 1 on page 487 of the "Crystallinity Determination" reference cited above. The AHf,c of a polymer is known to or can be obtained from it by those skilled in the art. The AHf,c of a sample polymer material can be based on the known AHf,c of a polymer material of the same or similar class, as known to those skilled in the art. For example, the AHf,c of polyethylene can be used to calculate the crystallinity of an EVA material because it is believed that the polyethylene backbone of the EVA rather than the vinyl acetate side chain portion of the EVA forms the crystals. Also by way of example, for a sample containing a blend of polymeric materials, the AHf,c of the blend can be estimated using a weighted average of the appropriate AHf,c for each of the individual classes of polymeric materials in the blend.
[0100] DSC measurements can be performed using a DSC thermal gradient of 10°C / min. The sample size for DSC can be 5-20 mg.
[0101] The multilayer film can be made by thermoplastic film forming methods known in the art. The film can be prepared by extrusion or coextrusion, using, for example, a tubular cut bubble film process or a flat film (i.e., cast film or slot die) process. The film can also be prepared by extrusion coating, adhesive lamination, extrusion lamination, solvent coating, or applying one or more layers by latex coating (e.g., spreading on a substrate and drying). Combinations of these methods can also be used.
[0102] For example, the film can be oriented in the machine direction (i.e., longitudinal direction), in the transverse direction, or in two directions (i.e., biaxial orientation) to enhance the strength, optical properties, and durability of the film. The film web or film tube can be uniaxially or biaxially oriented by applying a traction force at a temperature at which the film softens (e.g., above the Vicat softening point; see ASTM 1525) but below the melting point of the film. The film can then be rapidly cooled to maintain the physical properties generated during orientation and to provide the film with heat shrinkage properties. The film can be oriented using, for example, a tentering method or a bubble blowing method (double bubble blowing, triple bubble blowing, etc.). These methods are known to those skilled in the art and are therefore not discussed in detail herein. Orientation can occur in at least one direction at least about and / or at most about any of the following ratios: 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 12:1, and 15:1.
[0103] In an embodiment, the oxygen transmission rate of the multilayer film structure is no greater than: 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 200 0, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 3500, 3600, 3700, 3800, 3900 or 4000 cubic centimeters (at standard temperature and pressure) / square meter / day / 1 atmosphere oxygen pressure differential, measured at 0% relative humidity and 23°C according to ASTM D-3985, which is incorporated herein by reference in its entirety. In embodiments, the multilayer film structure has an oxygen transmission rate of less than 4000, 3000, 2000 or 1000 cubic centimeters (at standard temperature and pressure) / square meter / day / 1 atmosphere oxygen pressure differential, measured at 0% relative humidity and 23°C according to ASTM D-3985. Unless otherwise stated, the OTR values provided herein are measured at 0% relative humidity and a temperature of 23°C.
[0104] The minimum bonding strength of the film can be at least about any of the following: 2.5 N / 15mm, 3.0 N / 15mm, 3.5 N / 15mm, 4.0 N / 15mm, 4.5 N / 15mm, or 5.0 N / 15mm. The minimum bonding strength between each of the plurality of layers of the film, measured according to ASTM F904, can be at least about any of the values in the preceding sentence.
[0105] The minimum bond strength between the middle layer and the layers immediately adjacent to the middle layer may be at least about any of 2.5 N / 15mm, 3.0 N / 15mm, 3.5 N / 15mm, 4.0 N / 15mm, 4.5 N / 15mm, or 5.0 N / 15mm as measured according to ASTM F904.
[0106] Film transparency (also referred to herein as film clarity) is measured according to ASTM D 1746-97 "Standard Test Method for Transparency of Plastic Sheets," published April 1998, which is incorporated herein by reference in its entirety. Results are reported herein as "Percent Transparency." The multilayer film may exhibit a transparency of at least 15%, or at least 20%, or at least 25%, or at least 30%, measured using ASTM D 1746-97.
[0107] Film haze values are measured according to ASTM D 1003-00 "Standard Test Method for Haze and Luminous Transmittance of Transparent Plastics," published July 2000, which is incorporated herein by reference in its entirety. Results are reported herein as "Haze Percent." The multilayer film may exhibit a haze of less than 7.5%, or less than 7%, or less than 6%, measured using ASTM D 1003-00.
[0108] Film gloss values are measured according to ASTM D 2457-97 "Standard Test Method for Specular Gloss of Plastic Films and Solid Plastics," published on January 10, 1997, which is incorporated herein by reference in its entirety. Results are reported herein as "gloss percentage." As measured using ASTM D 2457-97, the film may exhibit a gloss of 60% to 100%, or 70% to 90%.
[0109] Now turn to Figures 1A-1D , showing a method for dissipating a soluble tie layer from a multilayer film structure. The multilayer film is shredded, ground or prepared according to the APR tensile test standard PET-P-00 and placed in a caustic solution at elevated temperature. The shredded film pieces are subjected to a caustic solution (consisting of 1 wt% NaOH at a temperature of 85°C, using a 15 minute wash time as outlined in the APR tensile test standard PET-P-00).
[0110] Over time, the soluble adhesive layers 12 and 14 begin to separate from adjacent layers (e.g., Figure 1B As time goes on, as shown in the outer layer 11, inner layer 15 and outer layer 13) dissolve and dissipate. Figure 1C As shown in , the soluble bonding layers 12 and 14 are separated from the adjacent outer layers 11 and 13 so that the additional caustic solution 18 is in contact with the soluble bonding layers 12 and 14. Although the soluble bonding layer is shown separated from the outer layer, it should be understood that the soluble bonding layer can be separated from the inner layer or any adjacent layer. In addition, the soluble bonding layer can be dissolved in the solution before being separated from any one or both layers. As shown in Figure 1D As shown in , the soluble bonding layer has dissipated from the two adjacent layers. Figure 1D In the embodiment shown in , the inner layer 15 is also soluble in the caustic solution, and the only solids remaining in the solution are the outer layers 11 and 13. Although a 5-layer membrane structure is shown, the number of layers is not intended to be limiting, and Figures 1A-1D It is intended to demonstrate the dissipation of one or more soluble adhesive layers. It should be understood that there can be any number of layers and any number of soluble adhesive layers. In addition, the inner layer can also be soluble, or in some embodiments, remain suspended in the solution.
[0111] The remaining solid components can be filtered, washed, rinsed and collected. In embodiments, the purity of the insoluble components is at least 95%, 96%, 97%, 98%, 99% or 99.2%. The collected components can be sent for recycling or reuse. In some embodiments, the dissolved components can be precipitated from the solution and collected subsequently. If there are multiple solid components, the solid components can be separated by, for example, sinking / floating collection and other known process methods.
[0112] Now turn to Figure 2-12 , showing various exemplary embodiments of multilayer film structures. Although multiple embodiments are shown, it should be understood that the figures are not exhaustive of possible film structures containing soluble tie layers.
[0113] Figure 2 A three-layer film structure is described with two outer layers 21 held together by a soluble tie layer 22. The two outer layers 21 have the same composition. Figure 3 A three-layer film structure is described with two outer layers 31 and 33 held together by a soluble tie layer 32. The two outer layers 31 and 33 have different compositions. For example, one outer layer may be a polyester-containing structure, while the other is a polyethylene-containing structure.
[0114] Figure 4 A five-layer film structure is described with two outer layers 41 of the same composition. Two soluble tie layers 42 and 44 are bonded to the outer layer 41 on one side and to the inner layer 45 on the other side. It should be understood that the soluble tie layers 42 and 44 can be of the same or different composition. The inner layer 45 can be one or more inner layers and can include a barrier layer.
[0115] Figure 5 A five-layer film structure is described with two outer layers 51 and 53 of different composition. Two soluble tie layers 52 and 54 are bonded to the outer layers 51 and 53, respectively. The two soluble tie layers 52 and 54 are each bonded to an inner layer 55. It should be understood that the soluble tie layers 52 and 54 can be of the same or different composition. The inner layer 55 can be one or more inner layers and can include a barrier layer.
[0116] Figure 6 A five-layer film structure is described with two outer layers 61 of the same composition. A soluble tie layer 62 and an adhesive tie layer 64 are bonded to the outer layer 61 on one side and to an inner layer 65 on the other side. The adhesive tie layer 64 may be insoluble in caustic solution and provide additional bonding strength between adjacent layers. The inner layer 65 may be one or more inner layers and may include a barrier layer. In some embodiments, the inner layer 65 is soluble in caustic solution so that dissipation of the soluble tie layer 62 will enable the inner layer 65 to be exposed to the caustic solution to dissolve.
[0117] Figure 7 A five-layer film structure is described with two outer layers 71 and 73 of different composition. A soluble bonding layer 72 and an adhesive bonding layer 74 are bonded to the outer layers 71 and 73 on one side, respectively, and bonded to an inner layer 75 on the other side. The adhesive bonding layer 74 may be insoluble in caustic solution and provide additional bonding strength between adjacent layers. The inner layer 75 may be one or more inner layers and may include a barrier layer. In some embodiments, the inner layer 75 is soluble in caustic solution so that dissipation of the soluble bonding layer 72 will enable the inner layer 75 to be exposed to the caustic solution to dissolve.
[0118] Figure 8 A six-layer film structure is described with two outer layers 81 and 83, which may be of the same or different composition. Soluble tie layers 82 and 84 are each bonded to an inner layer 85. Adhesive tie layer 86 is bonded to soluble tie layer 84 on one side and to outer layer 83 on the other side. Adhesive tie layer 84 may be insoluble in caustic solutions and provides additional bonding strength between adjacent layers. Inner layer 85 may be one or more inner layers and may include a barrier layer.
[0119] Fig. 9 A six-layer film structure is described having two outer layers 91 and 93, which may be of the same or different composition. Soluble tie layers 92 and 94 are bonded to outer layers 91 and 93, respectively. Soluble tie layer 92 and adhesive tie layer 96 are bonded to inner layer 95. Adhesive tie layer 94 may be insoluble in caustic solutions and provide additional bonding strength between adjacent layers. Inner layer 95 may be one or more inner layers and may include a barrier layer.
[0120] Fig.10 A seven-layer film structure is described with two outer layers 101 and 103, which may be of the same or different composition. Soluble tie layers 102 and 104 are bonded to outer layers 101 and 103, respectively. Two adhesive tie layers 106 and 107 are each bonded to inner layer 105. Adhesive tie layers 106 and 107 are bonded to soluble tie layers 104 and 102, respectively. Adhesive tie layer 104 may be insoluble in caustic solutions and provide additional bonding strength between adjacent layers. Inner layer 105 may be one or more inner layers and may include a barrier layer.
[0121] Fig.11A seven-layer film structure is described having two outer layers 111 and 113, which may be of the same or different composition. Soluble tie layers 112 and 114 are bonded to inner layer 115. Adhesive tie layer 117 is bonded to outer layer 113 on one side and to another inner layer 116. Inner layers 115 and 116 may be of the same or different composition. Adhesive tie layer 117 may be insoluble in caustic solutions and provide additional bonding strength between adjacent layers. Inner layers 115 and 116 may be one or more inner layers and may include barrier layers.
[0122] Fig.12 An eight-layer film structure is described with two outer layers 121 and 123, which may be of the same or different composition. A soluble bonding layer 122 is bonded to the outer layer 121 and an adhesive bonding layer 128. Adhesive bonding layer 128 is bonded to the soluble bonding layer 122 and the inner layer 125. A soluble bonding layer 124 is bonded to the inner layer 125 on one side and to the inner layer 126 on the other side. Adhesive bonding layer 127 is bonded to the inner layer 126 on one side and to the outer layer 123 on the other side. The inner layers 125 and 166 may be of the same or different composition. Adhesive bonding layer 127 may be insoluble in caustic solutions and provide additional bonding strength between adjacent layers. The inner layers 125 and 126 may be one or more inner layers and may include barrier layers.
[0123] In an embodiment, by Fig.13 The blown film process described in the figure produces films, which shows a schematic diagram of the process for making "hot-blown" films, which are oriented in the molten state and are therefore not heat shrinkable. Fig.13 Only one extruder 139 is illustrated, it should be understood that more than one extruder may be utilized to prepare the film.
[0124] exist Fig.13 In the method, extruder 530 supplies molten polymer to annular die 531 to form a film, which can be a single layer or a multilayer, depending on the design of the die and the arrangement of one or more extruders relative to the die, as known to those skilled in the art. The extruder 530 is supplied with polymer pellets suitable for forming a film. The extruder 530 subjects the polymer pellets to sufficient heat and pressure to melt the polymer and forward the molten stream through the annular die 531.
[0125] Extruder 530 is equipped with filter screen 532, perforated plate 533 and heater 534. Film is extruded between mandrel 535 and die head 531, and the obtained extrudate is cooled by cold air from air ring 536. The molten extrudate is immediately blown into bubble 537 to form a melt-oriented film. When the melt-oriented film moves upward along the length of bubble 537, it cools and solidifies. After solidification, the film tube passes through guide roller 538 and collapses into a flat fold structure by roller 539. Optionally, the collapsed film tube is passed through processor rod 540, then through idler roller 541, and then around tension adjustment roller 542, which gives the collapsed film tube 543 tension control, and the collapsed film tube 543 is wound into roller 544 via winder 545 afterwards. Example
[0126] The following materials were used to prepare the example structures described herein.
[0127] Material Code describe EAA1 is an ethylene / acrylic acid copolymer having more than 20% by weight of comonomer EAA2 is an ethylene / acrylic acid copolymer having about 15% by weight of comonomer EMA1 Ethylene / methyl acrylate copolymer EMA2 Ethylene / methyl acrylate copolymer EMAA1 It is an anhydride modified ethylene acrylate copolymer PA1 It is a hot melt polyamide sold under the trade name Uni-Rez 2720 PET1 It is a copolyester based on terephthalic acid, ethylene glycol and 1,4-cyclohexanedimethanol. PLA1 It is a plasticizer PS1 Polysorbate 60 ROS1 It is hydrogenated rosin SPE1 It is sulfopolyester TPS1 It is a thermoplastic starch barrier layer containing PVOH and high amylose starch
[0128] The approximate dissolution rate of the soluble bonding layer was determined by measuring the dissolution rate of the pellets used to prepare the structure. First, the diameter of 20 pellets was measured and the maximum diameter was recorded. The pellets were then placed in a 1% NaOH solution and stirred vigorously according to the APR draw-down test standard PET-P-00 (1 wt% NaOH, 85°C). The time for all pellets to dissolve was then recorded. The dissolution time was divided by the pellet diameter to obtain the dissolution rate expressed in in / min.
[0129] As in Figures 1A-1D As shown in , the dissolution of the soluble bonding layer is assumed to be mainly one-dimensional, wherein dissolution occurs only at the exposed edges of the structure. It is also assumed that the dissolution rate is constant over time and has nothing to do with the diameter of the change. Therefore, the width of the ground flakes specified by the APR draw-down test standard PET-P-00 is a maximum of 0.375 inches, and is used to determine the time taken for the soluble bonding layer to be completely dissolved from the structure. However, it should be noted that the recycling of the real world is largely uneven, resulting in different single flake sizes, shear rates, etc., which may affect the total dissolution time in the system. For example, if the flake layer is sheared apart to cause the soluble bonding layer to be fully exposed, dissolution can occur much faster. Therefore, in the embodiments disclosed herein, the minimum dissolution rate of the soluble bonding layer is at least 0.004 in / min.
[0130] The dissolution rates of various soluble adhesive formulations are shown in Table 2 below.
[0131] Table 2 - Linear dissolution rates of various soluble binder resin blends
[0132] Sample ID preparation Linear dissolution rate Notes Soluble Adhesion 1 (W) 80% (60% neutralized EAA1) / 20% ROS1 0.006in / min Soluble Adhesion 2 (W) 90% (60% neutralized EAA1) / 10% ROS1 0.0055in / min Soluble Adhesive 3 100% (60% neutralized EAA1) 0.004in / min Soluble Adhesion 4 (W) 80% (60% neutralized EAA1) / 20% SPE1 0.0065in / min Soluble Adhesion 5 (W) 90% (60% neutralized EAA1) / 10% SPE1 0.005in / min Soluble Adhesive 6 (C) 60% (60% neutralized EMA1) / 40% ROS1 <0.0025 in / min Incomplete dissolution Soluble Adhesive 7 (C) 80% (60% neutralized EAA1) / 20% EMAA1 <0.0025 in / min Incomplete dissolution Soluble Adhesive 8 (C) 90% EMAA1 / 10% PLA1 <0.0025 in / min Incomplete dissolution Soluble Adhesion 9 (W) 50% (60% neutralized EAA1) / 10% EAA2 / 20% ROS1 / 30% EMAA1 0.015 in / min Soluble Adhesive 10 (C) 69% EMA1 / 25% ROS1 / 6% KOH <0.0025 in / min Soluble Adhesion 11 (W) 64% EMA1 / 25% ROS1 / 5% PS1 / 6% KOH - Quickly split and disperse Soluble Adhesion 12 (W) 20% EMAA1 / 20% ROS1 / 40% (60% neutralized EAA1) / 20% EAA2 >0.02in / min Soluble Adhesion 13 (W) 28% EMAA1 / 20% ROS1 / 40% EAA1 / 10% EAA2 / 12% KOH - Very fast dissolving Soluble Adhesion 14 (W) 30% ROS1 / 5% PS1 / 35% PA1 / 30% neutralized EAA1 - Very fast dissolving Soluble Adhesive 15 (C) 50% EMA1 / 50% EMA2 <0.0025 Insoluble Soluble Adhesive 15 (C) 50% EMAA1 / 50% neutralized EAA1 <0.0025 Does not dissolve within a reasonable time frame Soluble Adhesive 16 (C) 50% EMAA1 / 50% ROS1 <0.0025 Does not dissolve within a reasonable time frame, low viscosity
[0133] Table 3 - Example Structure 1 ("Double-Sided")
[0134] Outer PET layer PET1 Adhesion and bonding 1 EMAA1 Soluble adhesive 1 80% (60% neutralized EAA1) / 20% ROS1 Barrier layer TPS1 Soluble Adhesive 2 80% (60% neutralized EAA1) / 20% ROS1 Adhesion bonding 2 EMAA1 Outer PET layer PET1
[0135] Example structure 1 is a seven-layer structure. One side of the entire structure is formed and coated onto a prefabricated barrier screen using an extrusion coating process. The structure is then moved to a second coating station where the other side is coated to obtain a complete structure as shown in Table 3 above.
[0136] Table 4 - Example Structure 2 ("Single-Sided")
[0137] Outer PET layer PET1 Adhesion and bonding EMAA1 Soluble adhesive 1 80% (60% neutralized EAA1) / 20% ROS1 Barrier layer TPS1 Adhesion and bonding EMAA1 Outer PET layer PET1
[0138] The soluble tie layer must also demonstrate good adhesion / bonding strength to both adjacent layers. Typically, multilayer films require a minimum of 1 lbf / in, and in some applications, as high as 4-7 lbf / in. The adhesion of various structures is shown in Table 5 below. In these cases, the failure point occurred between the soluble tie layer and the barrier layer, so it can be assumed that the bond strength between the other layers is stronger than the failure strength recorded.
[0139] Films for bond strength testing were produced on a flat cast extrusion line and then laminated to a barrier layer using a 1" wide heat sealer (130°C, 80 psi, 5 seconds heating time). The samples were then tested for bond strength on an Instron machine according to ASTM F904. All samples were tested in triplicate.
[0140] Table 5 - Bond Strength
[0141] structure Bonding strength PET1 / [70% EMAA1 / 30% EMA2] / [80% neutralized EAA1 + 20% ROS1] / TPS1 5.3lbf / in PET1 / [70% EMAA1 / 30% EMA2] / [90% neutralized EAA1 + 10% ROS1] / TPS1 5.0lbf / in PET1 / EMAA1 / [90% neutralized EAA1 + 10% AQ48 Ultra] / TPS1 8.9lbf / in PET1 / EMAA1 / [90% neutralized EAA1] / TPS1 ~0lbf / in PET1 / EMAA1 / [50% EMAA1 / 50% neutralized EAA1] / TPS1 ~0lbf / in PET1 / [25% ROS1 / 5% PS1 / 40% PA1 / 30% polyethyloxazoline] / TPS1 Adhesion to TPS1 but not to PET1 PET1 / [30% ROS1 / 5% PS1 / 35% PA1 / 30% neutralized EAA1] / TPS1 Adhesion to two layers PET1 / [15% Castor Wax / 20% ROS1 / 20% Neutralized EAA1 / 20% EAA2 / 5% PS1 / 20% Polyethyloxazoline] / TPS1 Glued to TPS1, lightly fixed to PET1 PET1 / [50% EMAA1 / 50% neutralized EAA1] / TPS1 N / A PET1 / Neutralized EAA1 / TPS1 N / A PET1 / [69% EMA1 / 25% ROS1 / 6% KOH] / TPS1 N / A PET1 / [64% EMA1 / 25% ROS1 / 5% PS1 / 6% KOH] / TPS1 Glued to TPS1, lightly fixed to PET1
[0142] A soluble tie layer having sufficient bond strength and dissolution rate was laminated to the barrier layer to produce a structure similar to that shown in Example Structure 1. These seven-layer structures were then tested according to the APR cycle protocol as outlined in PET-CG-01. In addition, several structures were produced according to Table 4. These structures incorporated a soluble tie layer on only one side of the barrier material. The structures produced according to Table 1 are labeled "double-sided", while the structures produced according to Table 2 are labeled "single-sided".
[0143] Starch was chosen as a barrier layer to easily identify impurities during the testing protocol. It should be understood that any suitable barrier layer can be used with the soluble bonding layer. The baking step of the PET-CG-01 protocol causes any residual starch contaminants to burn and turn brown. The brown color allows for a quick assessment of impurity levels. After this baking step, the brown contaminants are separated from the transparent flakes and the weights of the clean flakes and the contaminant flakes are recorded. The total contamination rate of the remaining barrier starch in the flakes is then calculated based on the known weight percentage of the overall structure. The results of the washing protocol and the resulting contamination levels are shown in Table 5 below.
[0144] structure Contamination rate PET1 / EMAA1 / (80% neutralized EAA1 / 20% SPE1) / TPS1 / EMAA1 / PET1 <1% PET1 / EMAA1 / (90% neutralized EAA1 / 10% SPE1) / TPS1 / EMAA1 / PET1 <1% PET1 / EMAA1 / (90% neutralized EAA1 / 10% SPE1) / TPS1 / (90% neutralized EAA1 / 10% SPE1) / EMAA1 / PET1 <0.5% PET1 / EMAA1 / (80% neutralized EAA1 / 20% ROS1) / TPS1 / EMAA1 / (80% neutralized EAA1 / 20% ROS1) / EMAA1 / PET1 <1%
[0145] This written description uses examples to disclose the invention, including the best mode, and also to enable those skilled in the art to practice the invention, including making and using any device or system and performing any combined method. The patentable scope of the invention is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if they have structural elements that do not differ from the literal language of the claims, or if they include equivalent structural elements that do not differ substantially from the literal language of the claims.
Claims
1. An extruded multilayer film comprising: a. First outer layer; b. a first soluble tie layer adhered to two adjacent layers, the first soluble tie layer comprising at least 40 wt % of ethylene acrylic acid copolymer, ethylene methacrylic acid copolymer or blends thereof, 20-90% of which is neutralized; and c. second outer layer; The first soluble adhesive layer is disposed between the first outer layer and the second outer layer, the first soluble adhesive layer being adhered to the two adjacent layers, wherein the bond strength is at least 2.5 N / 15mm, 3.0 N / 15mm, 3.5 N / 15mm, 4.0 N / 15mm, 4.5 N / 15mm or 5.0 N / 15mm as measured according to ASTM F904 Wherein when the multilayer film is prepared and tested, the first outer layer and the second outer layer remain solid and at least 90 weight percent of the first soluble tie layer dissipates from the multilayer film in a caustic solution containing 1 weight percent sodium hydroxide within 30, 25, 20 or 15 minutes at a temperature of 45°C, 55°C, 65°C, 75°C, 85°C, 95°C, and the remaining parameters are in accordance with APR Tensile Test Standard PET-P-00.
2. The multilayer film of claim 1, wherein the first soluble tie layer further comprises up to 30 wt% of a modified linear low density polyethylene or ethylene methyl acrylate.
3. The multilayer film of any of the preceding claims, wherein the ethylene acrylic acid copolymer is 20-90%, 30-80%, or 40-70% neutralized by addition of KOH or NaOH and the ethylene acrylic acid copolymer comprises 0.1-4% maleic anhydride grafting.
4. The multilayer film of any of the preceding claims, wherein the multilayer film further comprises a first inner layer disposed between the first soluble tie layer and either the first outer layer or the second outer layer, wherein the second outer layer comprises polyethylene terephthalate, the first inner layer is a barrier layer, and the first soluble tie layer is directly adhered to the second outer layer and the first inner layer.
5. The multilayer film of any of the preceding claims wherein the first soluble tie layer further comprises one or more of up to 30 wt% of a sulfopolyester, up to 40 wt% of a caustic soluble rosin modifier, and up to 10 wt% of a plasticizer, the plasticizer being glycerol.
6. The multilayer film of any of the preceding claims, wherein the first outer layer and / or the second outer layer comprises polyethylene terephthalate or polyethylene.
7. The multilayer film of claim 4, wherein the first inner layer comprises a barrier material selected from the group consisting of ethylene vinyl alcohol, polyvinyl alcohol, thermoplastic starch, polyvinylidene chloride, and polyamide.
8. The multilayer film of any of the preceding claims, further comprising a second tie layer comprising at least 10 wt% of an ethylene acrylic acid copolymer that has been 20-90% neutralized by the addition of KOH or NaOH, wherein the second tie layer has the same composition as the first soluble tie layer.
9. The multilayer film of any of the preceding claims, wherein the multilayer film comprises a plurality of barrier layers, wherein the plurality of barrier layers have different compositions.
10. The multilayer film of claim 7, further comprising: a. directly adhered to the first inner layer of the second soluble adhesive layer; b. a polyethylene terephthalate layer directly adhered to the second soluble adhesive layer; c. an adhesive tie layer comprising polyethylene directly adhered to the polyethylene terephthalate layer; and d. An outer layer of polyethylene adhered directly to the adhesive tie layer.
11. The multilayer film of claim 4, wherein the second outer layer comprises polyethylene terephthalate, the first inner layer is a barrier layer, and the first soluble tie layer is directly adhered to the first inner layer and a first adhesive tie layer, the first adhesive tie layer is directly adhered to the second outer layer and constitutes less than 10 weight percent of the multilayer film.
12. The multilayer film of claim 11, further comprising: a. directly adhered to the first inner layer of the second soluble adhesive layer; b. a second adhesive bonding layer directly adhered to the second soluble bonding layer; c. a polyethylene terephthalate layer directly adhered to said second adhesive tie layer; and comprising: d. a third adhesive tie layer comprising polyethylene directly adhered to the polyethylene terephthalate layer; and e. An outer layer of polyethylene adhered directly to the third adhesive tie layer.
13. The multilayer film of any of the preceding claims, wherein the first soluble tie layer has a dissolution rate of at least 0.004 in / min when placed in a NaOH solution at 85°C according to APR Tensile Test Standard PET-P-00.
14. The multilayer film of any of the preceding claims, wherein the first soluble tie layer comprises at least 50 wt% ethylene acrylic acid copolymer, ethylene methacrylic acid copolymer, or blends thereof, which are 20-90% neutralized.
15. A method for separating at least one layer of a multilayer membrane, comprising the steps of: a. providing a multilayer film by extrusion; the multilayer film comprising a first outer layer and a second outer layer and a soluble tie layer adhered to two adjacent layers, the soluble tie layer comprising at least 40% by weight of an ethylene acrylic acid copolymer, 20-90% of which is neutralized; b. chopping or grinding the multilayer film; c. subjecting the multilayer membrane to a caustic solution for at least 30, 25, 20, 15 or 10 minutes; the caustic solution being at an elevated temperature in any one of the following ranges or between any one of the following ranges: 40-50°C, 50-60°C, 60-70°C, 70-80°C, 80-90°C, 90-100°C, to cause the soluble tie layer to dissipate from the multilayer membrane, resulting in dissolved components and solid components of the multilayer membrane in the caustic solution; and d. collecting the solid component from the caustic solution; wherein in the caustic solution, the first outer layer and the second outer layer remain solid and at least 90 weight percent of the soluble tie layer dissipates from the multilayer film.
16. The method of claim 15, wherein the soluble tie layer comprises at least 50% by weight of ethylene acrylic acid copolymer, ethylene methacrylic acid copolymer, or blends thereof, which are 20-90% neutralized.
Citation Information
Patent Citations
Composition comprising ethylene - acrylate copolymer and polyolefin and tackifier
CN101052676A
Adhesive Acrylate-Olefin Copolymers, Methods for Producing Same and Compositions Utilizing Same
US20130048221A1
pH sensitive thermoplastic binder
US6077895A
Degradable polymers
US6162852A
Separation / recovery method for laminated film
WO2020066652A1